Teacher Readiness Instrument for Culturally Responsive Teaching (CRT) in Papua Border Schools: Construct Validity, Reliability, and Measurement Invariance - Aisyah Ali; Akhmad Kadir; Ria Ristiani (Postgraduate, University of Mataram, 2025)
This study addressed the need to strengthen science literacy in the Indonesia–Papua New Guinea border region through Culturally Responsive Teaching (CRT) by developing and validating a context-appropriate teacher readiness instrument for indigenous communities. The instrument was specified as a multidimensional model encompassing pedagogical knowledge, efficacy, school contextual support, culturally responsive planning and materials, culturally responsive assessment, and community collaboration. A layered, cross-sectional validation was conducted: expert judgment for content validity, target-user assessment for face validity/readability, a limited pilot (approximately 30 respondents), and confirmatory factor analysis (CFA) on the main sample; measurement invariance (MI) across gender, years of service, and certification was tested sequentially. Content validity met predefined standards: all items achieved I-CVI ≥ .78 and S-CVI/Ave = .917; qualitative feedback prompted the alignment of terminology and local examples without altering construct coverage. Internal reliability was adequate (α and ω ≥ .70). CFA indicated acceptable fit; most loadings were ≥ .50; CR ≥ .70; AVE ≥ .50; and discriminant validity was satisfied. Measurement invariance was established up to the scalar level for gender and certification, and up to the metric level for years of service; comparisons of latent means by years of service therefore require a partial scalar approach based on the problematic indicators. A known-groups test showed a practically meaningful difference between certified and non-certified teachers (Cohen’s d ≈ 0.63; p < .05). Overall, the instrument is culturally adapted and empirically validated, enabling program evaluation and targeted professional development toward inclusive, culturally responsive science education.